2021
DOI: 10.1155/2021/6621950
|View full text |Cite
|
Sign up to set email alerts
|

Motor Function Assessment of Upper Limb in Stroke Patients

Abstract: Background. Quantitative assessment of motor function is extremely important for poststroke patients as it can be used to develop personalized treatment strategies. This study aimed to propose an evaluation method for upper limb motor function in stroke patients. Methods. Thirty-four stroke survivors and twenty-five age-matched healthy volunteers as the control group were recruited for this study. Inertial sensor data and surface electromyography (sEMG) signals were collected from the upper limb during volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…Previous studies assessed the structural and functional muscle alternation after stroke by ultrasonography ( Kim et al, 2021 ), muscle biopsy ( Dalise et al, 2020 ), sEMG ( Hu et al, 2015 ), high-density-surface (HD-sEMG) ( Tanzarella et al, 2020 ), and dual-energy X-ray absorptiometry ( Choi et al, 2021 ). There are studies that applied sEMG, kinematic parameters, and clinical scales to evaluate the upper-limb motor function in stroke survivors ( Donoso Brown et al, 2014 ; Pan et al, 2021 ). But these studies focused only on the changes in the properties of muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies assessed the structural and functional muscle alternation after stroke by ultrasonography ( Kim et al, 2021 ), muscle biopsy ( Dalise et al, 2020 ), sEMG ( Hu et al, 2015 ), high-density-surface (HD-sEMG) ( Tanzarella et al, 2020 ), and dual-energy X-ray absorptiometry ( Choi et al, 2021 ). There are studies that applied sEMG, kinematic parameters, and clinical scales to evaluate the upper-limb motor function in stroke survivors ( Donoso Brown et al, 2014 ; Pan et al, 2021 ). But these studies focused only on the changes in the properties of muscles.…”
Section: Introductionmentioning
confidence: 99%
“… Formstone et al (2021) used a new combination of wearable inertial and mechanical mapping sensors to quantify motor function after stroke, demonstrating that the results of Fugl–Meyer assessment were consistent with those of the mapping sensors. Pan et al (2021) quantitatively assessed motor function in patients with stroke by collecting surface electromyography (sEMG) signals and inertial sensor data during the voluntary upward reach of the upper extremity. As evidenced by new publications in the last 3 years, the Fugl–Meyer scale has been widely used worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they found three muscle synergies that may explain reaching movement. Moreover, severe patients changed one of these muscle synergies; meanwhile, the mild-to-moderate patients were more similar to the control template [ 66 ]. Thus, individualized training may be developed to make the patients’ features more similar to the ones in control subjects so as to improve similarity values (i.e., Median-sp) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, our results demonstrate that muscle-synergy parameters showed a potential to contributing to discriminate between patients with different recovery potential: the relationship between neurophysiological parameters (i.e., Median-sp) and clinical variables at the beginning of therapy gave some indication about the potential patient-tailored treatment. More trials will be needed to define the real contribution of muscle-synergy parameters to distinguish between fitters and no-fitters of reactive neurobiological recovery [ 66 , 71 ]. Moreover, we may consider using the similarity parameter (i.e., Median-sp) to build patient-specific prediction models to improve clinical decisions, and, ultimately, recovery and outcome after stroke [ 72 ].…”
Section: Discussionmentioning
confidence: 99%